Administrative responsibility for violations in the protection of public morals - Новицька, Н. Б. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article the problems of establishment of administrative responsibility are examined for offence inthe sphere of defence of public moral and the ways of perfection of current legislation are outlined in themarked sphere.